KETIDAKSESUAIAN HARAPAN MELALUI COMPUTER MEDIATED COMMUNICATION PADA STUDI KASUS PENGGUNA FAKE ACCOUNT DI TWITTER - Kevin Krisna Tambunan (2023)
One of the uses of social media is fake accounts, in reality, communication through cyberspace often occurs forgery of self-identity. False identity allows frequent mismatch expectations in interactions. This research aims to examine the discrepancy between the expectations of users of fake accounts on Twitter and the process of Computer-Mediated Communication (CMC) in using fake accounts on Twitter. Research using CMC theory. In every interaction with new people, individuals have personal expectations that produce a communicative impact if these expectations are not appropriate. This study used qualitative research methods. Research data was obtained through a process of observation, documentation, and interviews with 6 active fake account users who have experience with other fake account users. The results of the study concluded that the informants created fake accounts because they wanted to know and tried to express what they felt. The existence of self-freedom without having to be known by others. The reason for the discrepancy in expectations is because of disappointment with fake account users when interacting on social media by playing and using fake identities